Sport, Performance and Sustainability - Svensson, Daniel; Backman, Erik; Hedenborg, Susanna; Sörlin, Sverker (Routledge Research in Sport, Culture and Society, 2023)
This book examines the logic of 'faster, higher, and stronger' and the technoscientific revolution that has driven tremendous growth in the sports economy and in sport performance over the last 100 years. It asks whether this logic needs revisiting in the light of the climate crisis and sport's environmental responsibilities. Drawing on multi-disciplinary work in sport history, sport pedagogy, sport philosophy, sport science, and environmental history, the book considers not only how sportification may have contributed to the growing environmental impact of sport but also whether it might be used as a tool of positive social change. It reflects on the ways that sport sets performance limits for other ethical reasons, such as doping controls, and asks whether sport could or should set limits for environmental reasons too. Sport, Performance and Sustainability touches on key themes in sport studies, including digitisation, activism, social media, empowerment, youth sport, and physical education. This is fascinating reading for anybody with an interest in sport, the environment, development, sociology, or culture. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution 4.0 license.